المرجعيات الثقافية بين المفهوم والتوظيف - سبيعي، حكيمة; هولي، خولة بوزياني (جامعة الشهيد حمه لخضر الوادي, 2019)
الهدف من هذه الدراسة إزالة اللبس عن مصطلح المرجعية الثقافية، نظرا لما لقيه من تعدد وتضارب في الآراء التي سعت إلى تقديم طرح خاص به، نحن بدورنا نقدم ونعرض مفهوم المرجع من خلال المقاربات اللغوية في المعاجم العربية والغربية، وكذا البحث في ذاكرة هذا المصطلح. كما وسنزيل الستار عن بعض المصطلحات مثل الثقافة، والفرق بين المرجع والمرجعية، وكيف انتقل الدارسون والباحثون من الدراسات الثقافية في شتى المجالات إلى توسيعه وطرحه في المجال الأدبي، ليظهر لنا مفهوم آخر استمد مبادئه من الدراسات الثقافية المقدمة سابقا، وهو النقد الثقافي كمنهج جديد ظهر عوضا عن النقد الأدبي أو بعده. وعليه سنقف عند مفهوم هذا المنهج، وكيف أن له دورا بارزا في تحديد آليات ومبادئ المرجعيات الثقافية التي تبنى عليها النصوص الأدبية في كثير من الأحيان، هذا إذا نظرنا للنص على أنه بنية ثقافية تكتنز العديد من الأنساق التي من شأنها أن تكشف لنا عن تفكير أمة وعاداتها وتقاليدها وأيديوجيتها في مختلف المجالات، خصوصا وأن أغلب الدراسات تجمع على أن النص عبارة عن مجموعة من الشحنات الدلالية التي ينبغي فك شفراتها.
The aim of this study is to remove the ambiguity from the term cultural reference, because of the multiplicity and conflict of opinion that sought to present a specific proposition. We, in turn, present and present the concept of reference through linguistic approaches in Arabic and Western dictionaries, as well as research into the memory of this term. We will also remove some of the terms such as culture, the difference between reference and reference, and how scholars and researchers moved from cultural studies in various fields to expand and put it in the literary field, to show us another concept derived from the previous cultural studies, cultural criticism as a new method instead of Literary Criticism or Beyond. Therefore, we will stand at the concept of this approach, and how it has a prominent role in determining the mechanisms and principles of cultural references on which literary texts are often based, if we look at the text as a cultural structure to acquire many patterns that would reveal to us the thinking of a nation and its customs and their traditions and ideologies in various fields, especially since most studies gather that the text is a set of semantic shipments that should be decoded.
Keywords: المرجعيات الثقافية -- النقد الثقافي -- النقد الأدبي